Misidentified Victim-Survivors as Domestic and Family Violence Perpetrators: Plea Negotiations as a Tool for Justice? - Moffa, Monique (The British journal of criminology, 2025)
The misidentification of primary perpetrators in domestic and family violence (DFV) incidents has received increased attention in academic, practitioner and policy contexts. Yet limited research has explored the implications of misidentification for women in criminal proceedings, specifically how misidentification and subsequent criminalisation of women are linked to both erroneous or forced guilty pleas, and a reliance on plea negotiations to correct misidentification errors. Drawing on interviews with 21 legal defence practitioners, we document the strategies practitioners use in the plea negotiation process to advocate for women defendants who have been misidentified in DFV contexts. We also explore the barriers that women defendants face in accessing justice in a discretionary and managerialist criminal justice system.